P213 Long term results of concurrent chemotherapy and hypofractionated radiotherapy for inoperable NSCLC. (16th November 2010) - Maguire, J; Kelly, V; Smyth, C; Ledson, M; Walshaw, M
Abstract : Concurrent chemoradiation is an effective form of treatment for inoperable stage 3 NSCLC, with a survival advantage in meta-analyses compared to standard chemotherapy and radiotherapy. However, reported local tumour control (LTC) rates are less than 40%. US studies aim to improve LTC by radiotherapy dose escalation and the addition of cetuximab. An alternative approach is to deliver radical radiotherapy concurrent with chemotherapy within a 4-week period, aiming to minimise the effects of accelerated repopulation and thus enhance LTC and survival. We have treated 104 NSCLC patients with cisplatinum (30 patients) or cisplatinum and vinorelbine (74 patients) concurrently with 50–55Gy in 20 fractions over 26 days. Two-thirds of the patients were male, one third female; median age was 64. 90 patients had stage 3 NSCLC, 12 patients had inoperable stage 2 disease, and 2 had stage 4 disease. 84 patients were PS 0-1, 18 PS 2 and 2 PS 3. 64 patients received between two and four cycles of chemotherapy after completion of concurrent treatment. Median survival for the whole group was 23 months. Survival rates at 3, 5 and 10 years (all causes mortality) were 41.7%, 30.1% and 16.2%. Chemotherapy after concurrent treatment increased median survival (26.6 vs 14.6 months) and survival at 2 years (53.1% vs 40%) but made no difference to survival at three and 5 years. There was an advantage for patients who received 55Gy compared to those who received 50–52.5Gy, with median survival of 37.9 months versus 20.6 months, 2-year survival 64.2% versus 40%, 3-year survival 56.2% versus 34.2% and 5-year survival 36% versus 28.5%. The local tumour control rate was 76% for patients receiving 55Gy and 68.6% for patients receiving 50–52.5 Gy. There were no treatment related deaths. 86 patients developed grade 2 oesophagitis, nine patients suffered grade 3 oesophagitis and eight patients required dilation of oesophageal stricture between 8 weeks and 3 years after treatment. Chemoradiation usingaccelerated hypofractionated radiotherapy concurrent with cisplatinum and vinorelbine enhances local control and survival for patients with locally advanced NSCLC and good performance status.